PHONETIC INFORMATION IN MATERIALS FOR LEARNING UKRAINIAN BY FOREIGNERS - Haidysh, N. (Linguistic and Conceptual Worldviews, 2019)
In the article, phonetic material is analyzed in terms of its interpretation in textbooks and in- teractive means for learning Ukrainian as a foreign language. Language learning begins with the acquaintance with its phonetic system. So properly presented phonetics makes the process of language understanding not only possible but more available during studies. While considered from this point, phonetics is described a constituent part of a language system. For this system to take in use easier, language materials aimed at foreigners have to describe phonetics with the help of audio records and visual schemes. Visualization of a language apparatus work along with voice records helps to de- velop typical Ukrainian pronunciation. The point is that quite a few of sources give the opportunity tounderstand the phonetics through these methods. The language learning sources mostly do not provide a foreigner with audio-visual explanations. If the materials contain physiological pictures of language organs’ positions and voice records, a learner becomes able to understand the diﬀerence between their native phonetic system and the foreign (Ukrainian) one. The author of the article proves that for completing representative schemes, findings from the experimental phonetics have to be included. So using audio-visual additions is made possible due to researches in this branch. Moreover, it is proven that incompletely presented sound system causes accent development. Argumentatively the necessity of forming new materials is described as well as a renovation of those that already exist. Conclusions are made on the basis of comparative analysis of available sources for language learning.
Keywords: experimental phonetics, accent, articulation, audio-visual additions, interactive means